Eliminating Chagas disease: challenges and a roadmap. (14th April 2009) - Reithinger, Richard; Tarleton, Rick L; Urbina, Julio A; Kitron, Uriel; Gürtler, Ricardo E
Abstract : Millions of people in Central and Southern America are affected by Chagas disease. Richard Reithinger and colleagues explain the difficulties of elimination and suggest a strategy